2016
DOI: 10.3389/fphys.2016.00153
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Effects of Zinc Chloride on the Bone Development in Danio rerio (Hamilton, 1822)

Abstract: The increase of heavy metals in the environment involves a high exposure of aquatic organisms to these pollutants. The present study is planned to investigate the effects of zinc chloride (ZnCl2) on the bone embryonic development of Danio rerio and confirm the use of zebrafish as a model organism to study the teratogenic potential of this pollutant. Zebrafish embryos were exposed to different ZnCl2 concentrations and analyzed by ICP-MS. The skeletal anomalies were evaluated to confocal microscope after stainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 22 publications
2
27
0
Order By: Relevance
“…In this paper, we identified three red fluorescent dyes in the 9,10-anthraquinone family of compounds (lucidin, purpurin and 3-hydroxy-morindone) that can be used to stain and trace developing bones in live vertebrates. These dyes can be applied directly to live animals with significant advantages over the traditional Alizarin Red-staining on fixed samples, and even the green fluorescent bone dye calcein ( Salvaggio et al, 2016 ), as these compounds emit at a longer wavelength.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, we identified three red fluorescent dyes in the 9,10-anthraquinone family of compounds (lucidin, purpurin and 3-hydroxy-morindone) that can be used to stain and trace developing bones in live vertebrates. These dyes can be applied directly to live animals with significant advantages over the traditional Alizarin Red-staining on fixed samples, and even the green fluorescent bone dye calcein ( Salvaggio et al, 2016 ), as these compounds emit at a longer wavelength.…”
Section: Discussionmentioning
confidence: 99%
“…Several organisms are used as models in toxicological studies (Conte et al, 2016;Copat et al, 2012;D'Agata et al, 2014;De Domenico et al, 2011;Kanold, Wang, BrĂŒmmer, & Ć iller, 2016;Mazzei et al, 2014;Scuderi et al, 2014;Wang, Jia, Zhu, Zhang, & Wang, 2017;Xiao, Vijver, Chen, & Peijnenburg, 2015), and among these, presently, zebrafish is considered the model organism, best suited, for toxicological testing Buccheri et al, 2016;Pecoraro et al, 2018;Pecoraro, D'Angelo, et al, 2017;Pecoraro, Salvaggio, et al, 2017;Salvaggio et al, 2016;Wang et al, 2011). Different types of parameters are used to evaluate NPs toxicity such as hatching F I G U R E 3 Scanning electron microscopy of the corneal surface reveals the presence of microvilli and microplicae and fingerprintlike structures.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies on animal models have shown that NPs can be potentially toxic (Hu et al, ; Lankveld et al, ), and that toxicity of NPs depends certainly on their size (Lankveld et al, ). Among the different animal models, zebrafish or Danio rerio is considered an excellent model for nanotoxicity studies for some particular features of these animals (Brundo et al, ; Lee, Nallathamby, Browning, Osgood, & Xu, ; Pecoraro et al, ; Pecoraro et al, ; Pecoraro et al, ; Salvaggio et al, ; Sarasamma et al, ; Zhao et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The use of zebrafish as animal model is recommended in several of these researches because it is an inexpensive, quick, and easy model to assess the nanoparticle toxicity [58], and it can offer many advantages for toxicological research [59,60]. In particular, ZFET, an alternative approach to acute toxicity testing, is important in order to decrease the impact of the experimental tests on live animals as well as suggested by the European Community.…”
Section: Discussionmentioning
confidence: 99%